KAJIAN PENDEKATAN ETNOPEDAGOGI DALAM PENDIDIKAN MELALUI KEARIFAN LOKAL ACEH - Fatmi, Nuraini; Fauzan, Fauzan (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2022)
The purpose of this study was to determine the ethnopedagogical approach in education, especially in aceh. The elements studied are Acehnese local wisdom in learning at school. This is in accordance with the problems found in the field through the author's initial observations at school, that so far the learning that has taken place does not link the concept of learning with local wisdom in the area. Thus the culture in the area becomes a taboo for the students themselves. So the ethnopedagogical element in learning at school is not introduced to students, in this case the integration of local wisdom in classroom learning has not been maximized, so far education and the value of local wisdom have not fully merged into a formidable new force in the body of education. The research method used is a descriptive qualitative research method that uses study content contained in various literatures as the primary data base. The data sources in this article are journals and books related to thematic learning and local wisdom education. Furthermore, the object of research is the adaptation process and its relation to local urgency in responding to the challenges of the times. Research results In this study, the ethnopedagogical approach is focused on education by introducing Acehnese local wisdom such as the Seudati dance which makes movement patterns in mathematics learning, Jeungki as a traditional tool that starting to be abandoned, even most of the millennial generation are no longer familiar with jeungki found in science learning, and what is related to history learning is the local wisdom of Peusijuek